Length-length, length–weight relationships and condition factor of Nile perch, Lates niloticus (Linnaeus, 1762) in the Pendjari River, West Africa. - AHOUANSOU, MONTCHO SIMON; LALEYE, PHILIPPE A. (My University, 2009)
This study is the first of its kind on the population of Lates niloticus from the Pendjari River (West Africa). It provides information on length frequency distributions, length-length, weight-length relationships and condition factor of the species. A total of 781 specimens were used for this study and were caught by artisanal fishing gears between Februay 2006 and January 2007. The length frequency distributions were unimodal. Individuals larger than 20.0 - 22.5 cm (modal class) were more abundant (71.06 %). Monthly, the coefficient b and the condition factor (K) ranged from 2.83 to 3.31 (mean = 3.14) and from 0.44 to 2.44 (1.14), respectively. The growth was in favour of the body weight (b>3, positive allometric growth) during the low water season and in favour of the length (b<3, negative allometric growth) during the high water season. Whenever possible, the b values for the species obtained both in this study and in some of the previously reported ones were compared. Generally, b values indicate a positive allometric growth for the species.
Keywords: Lates niloticus; length-weight relationships; condition factor; Pendjari River